BIOFILTRATION KINETICS OF TOFU INDUSTRY WASTEWATER USING OF ZEOLITE MEDIUM - Rodiyanti Rodiyanti; Sugeng Triyono; Nugroho Haryono (The University of Lampung, 2014)
This researchwas aimed to investigate reactionkinetic of tofu industrywastewater using zeolitemedium. A staticfilter reactor using zeolitemediumwas constructed to carry out this research. Tofuwastewaterwas resirculatedthrough themedium with various hydraulic retention times (HRT): 0, 3, 6, 12, 24, 36, and 48 hours. First orderreactionwas then applied on this kinetics. The results showed that pHincreased from4.1 to 8.02. Total P in thewastewater decreased from12,1mg/L to 6,91mg/L (42%reduction),while in themedia totalP increased from3,04 mg/L to 5,97 mg/L within 48 hours of filtration. N-NH4+ decreased from 64.184 mg/L to 12.85 mg/L(79.9%reduction). Total Solids decreased from 10.404mg/L to 4003m(61.5%reduction).